Pain assessment of ultrasound-guided liver biopsy for diffuse parenchymal diseases: a randomized trial comparing intercostal and subcostal techniques - Türk, Yaşar; Alıcıoğlu, Banu; Devecioğlu, İsmail (The European Research Journal, 2021)
Objectives: Percutaneous liver biopsy is widely used in diffuse liver parenchymal diseases. Comparison of the severity of pain is not properly studied. In this randomized study, pain intensity between the intercostal and subcostal techniques of US-guided Tru-Cut liver biopsy in diffuse liver diseases was compared. Methods: Between March 2016 and May 2017, all potential study participants referred to the interventional radiology department for ultrasound-guided liver biopsy (n = 245), were assessed for enrollment. The pain intensity at 0, 2, and 4 h post-procedure was compared in two groups using a Numeric Rating Scale (NRS). Premedication was not used. After applying local anesthesia under US-guidance, 18-G automatic biopsy needle free-hand US-guided biopsy was performed. Results: Immediately after the biopsy (p = 0.0024), and at the 2nd hour (p = 0.0298), NRS of the subcostal group was significantly less than the intercostal group. Furthermore, the need for oral (p = 0.0492) or intramuscular (p = 0.0094) analgesics after the biopsy in the subcostal group was significantly less than the intercostal group. At the evaluation of both groups together, 55.62% of the patients had a mild and 27.22% had a moderate pain score. NRS score decreased with time in each group. Conclusions: The pain intensity and the need for analgesics were less in the subcostal biopsies. Since intense pain and anxiety may be the cause of loss of the patients after the first biopsy, a subcostal biopsy could be preferred primarily.